Factors affecting household’s willingness to pay for the fish conservation zones a case study from Khong District, Champasak Province, Laos - Salongxay Fongsamouth,; Sakhone Keosoubinh,; Philavanh Homsombath,; Vilaphone Sounakeovongsa,; Vannasinh Souvannasouk,; Nitphone Senganatham,; Vanphakonekham Koulavongsa, (Maejo International Journal of Energy and Environmental Communication, 2022)
This research aims to estimate whether the WTP for fish conservation zones in terms of fish species protection areas. The authors used cross-sectional data that was collected from 369 respondents in 3 target villages in the Khong district of Champasak province Laos in 2021 and utilised WTP and maximum likelihood regression, marginal effect result for analysis. The estimate of the empirical model used for econometric analysis is based on the previously described model. This study finds that the average WTP households in target villages for fish conservation zones is 12.12 US $/household/year. The bid price, the recognition of the necessity of the fish conservation zones' knowledge, and average monthly income all positively impact WTP for fish conservation zones with a statistically significant impact. The authors conclude that the fish conservation zones might increase fish species in the study area. This valuation can be calculated as the cost to improve the quality of establishing fish conservation zones by multiplying the number of people in three villages of 768 households, which is the value expectation of the economy at 9,310 US $/year. However, improving public goods conservation now is the duty of everybody, so if we would like to strengthen fish conservation zones more efficiently than ever, we may find more suitable and sustainable alternatives.